Adult Orbital Xanthogranulomas: Clinical Features and Management. Issue 4 (July 2015) - Kiratli, Hayyam; Kiliç, Meltem; Tarlan, Berçin; Söylemezoğlu, Figen
Purpose: Adult-onset asthma with periocular xanthogranuloma and adult-onset xanthogranuloma are 2 rare subtypes of non-Langerhans cell histiocytic disorder and much remains unknown regarding optimal treatment. The authors describe their experience in the management of these 2 disease subtypes. Methods: This is a retrospective case series with histopathologically proven orbital xanthogranuloma over a period of 12 years. Clinical, imaging, and histopathologic features; associated systemic conditions; treatment modality; and outcome during follow-up of 6 adult patients who had adult-onset asthma with periocular xanthogranuloma and adult-onset xanthogranuloma were reviewed. Results: The age range was 29-75 years (median 56 years). The duration of symptoms and signs varied from 10 months to 9 years. All patients had bilateral and asymmetric involvement. Palpebral swelling with yellow discoloration and upper eyelid ptosis were the most common signs. Adult-onset asthma was present in 2 patients. Imaging studies demonstrated ill-defined infiltrative lesions involving the preseptal area, lacrimal glands, extraocular muscles, retrobulbar fat, and optic nerves. The median follow-up was 50 months. Complete regression of all clinical signs was obtained at 8 months, whereas imaging findings disappeared at 18 months with treatment. No recurrence was observed. Conclusions: Treatment consisting of debulking as much affected soft tissue as possible followed by a 3-day course of intravenous pulse methylprednisolone administration and then by oral prednisone for at least 6 months may provide adequate regression of the granulomas without recurrence and satisfactory cosmesis in patients with adult orbital xanthogranuloma with and without asthma.